Development of a strategy for integration of supply chain - Wong, Yoon Foo. (2008)
Integrated supply chain management has been recognized as a core competitive strategy. The benefits of integration are to add value, reduce waste, reduce cost, improve communication, achieve quick customer response and improve customer satisfaction. This dissertation includes feasibility studies for integration of supply chain through strategic alliance and factory automation.